PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE PADA MAHASISWA S1 AKUNTANSI PADANG - Renil Septiano (Sekolah Tinggi Pariwisata Mataram, 2022)
Abstract Purchasing decisions are conditions in which buyers purchase products or services based on consumer desires. This study aims to obtain empirical evidence whether there is an effect of brand image, price and product quality on purchasing decisions. The population of this study were students of Dharma Andalas University. The sampling used was nonprobability sampling with purposive sampling technique. Sampling using purposive sampling technique means that each individual who is used as a sample is chosen deliberately based on certain considerations, these considerations include the characteristics of the respondent himself. The characteristics applied in this study to select the sample in this study were students of Dharma Andalas University S1 Accounting for the year 2017-2019. Data collection was carried out using a questionnaire instrument. The analytical method used to test the hypothesis is multiple linear regression. The results of this study indicate that brand image affects purchasing decisions, price does not affect purchasing decisions, and product quality affects purchasing decisions.